ECOSYSTEM OF GOODS AND VALUE CREATION (International Seven Journal of Multidisciplinary, 2025)
This paper investigates how goods assembled form ecosystem that determines their values independently of the price system. While this aspect has roots in old classical economic theory, it has periodically been overlooked in the development of consumer theory. It draws inspiration from the assertions by M. Douglas and B. Isherwood that nothing possesses inherent value and focuses on approaches of making correct choices by G. Gigerenzer, as well as examples drawn from the marketing systems of supermarkets, superstores, hypermarkets, and mega malls, where a diverse array of products is made available to buyers. The findings of this study suggest that interconnected goods within an ecosystem establish standards of exchange-values that significantly contribute to consumer choice.